PATH ANALYSIS FAKTOR YANG MEMENGARUHI KETEPATAN PEMAKAIAN KONTRASEPSI SUNTIK DMPA BERDASARKAN REASONED ACTION THEORY (RAT) - Eniyati; Rahmawati, Dechoni; Yulaikhah, Lily (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
ABSTRACT Background:New family planning participants in Indonesia in 2015, 1,032,054 included 546,215 injections (52.93%), birth control pills totaling 252,091 (24.43%), condoms as many as 55,737 (5.40%), implants as many as 90,576 (8.87%), Intra-uterine Device (IUD) as many as 71,936 (6.97%), Female Operating Methods (MOW) as many as 14,590 (1.41%), Male Operating Methods (MOP) as many as 909 (0.09%). In Indonesia birth control by injection is the main choice for family planning acceptors (BKKBN, 2015). The highest percentage of new family planning participants in Central Java in 2016 was injection contraception of 5.4% (Health Profile of Central Java Province, 2016). Active KB participants in Magelang Regency in 2015 used the most non-long-term contraception method (MKJP) type injections, by 50.5%. The most new KB acceptors also use 56.9% injection contraception (Magelang District Health Profile, 2015). KB contraception is a way to prevent pregnancy through hormonal injections. Hormonal contraception by injection is more frequently used because of its effectiveness, practical use, cheaper price and safety. Objective:Analyzing the factors that influence the accuracy of DMPA injection KB acceptors based on reasoned action theory in PMB Dhiaulhaq Magelang Regency. Research ini variable attitudes, subjective norm, intentions and behavior. Methods:Analytic survey research using a cross sectional approach. The population in this study were all DMPA injection KB acceptors in PMB Dhiaulhaq Magelang. The sampling technique uses a case group and a control group that is fixied diseases sampling of 100 respondents. Data collection tool uses a questionnaire. Results:Perception directly affects the norm with a p value of 0.007. Norm directly affects attitude with a p value of 0.007. Attitude directly influences intention with a p value of <0.001. Intention directly affects the accuracy / usage with a p value of 0.012. Conclusion:The intention directly influences the behavior of the accuracy of visits in the use of DMPA injection KB. Attitude influence indirectly through intention. Subjective norma affect indirectly through attitude and intentions. Perception of control has an indirect effect through subjectifve norms, attitudes, and intentions. Keywords:Contraception, DMPA injection, Appropriate Usage